2009
DOI: 10.1016/j.visres.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Relative peripheral hyperopic defocus alters central refractive development in infant monkeys

Abstract: Understanding the role of peripheral defocus on central refractive development is critical because refractive errors can vary significantly with eccentricity and peripheral refractions have been implicated in the genesis of central refractive errors in humans. Two rearing strategies were used to determine whether peripheral hyperopia alters central refractive development in rhesus monkeys. In intact eyes, lens-induced relative peripheral hyperopia produced central axial myopia. Moreover, eliminating the fovea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
269
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(278 citation statements)
references
References 34 publications
7
269
1
1
Order By: Relevance
“…Moreover, optical manipulations of peripheral vision, which do not alter central vision, may be effective in controlling central refractive development. [51][52][53] Figure 1 Interocular differences in refractive error (treated eye correction À fellow eye correction) plotted as a function of age for individual monkeys reared with À 3D (left panel) or þ 3D lenses over one eye (middle panel). 22,46 The fellow eyes viewed through zero-powered lenses.…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, optical manipulations of peripheral vision, which do not alter central vision, may be effective in controlling central refractive development. [51][52][53] Figure 1 Interocular differences in refractive error (treated eye correction À fellow eye correction) plotted as a function of age for individual monkeys reared with À 3D (left panel) or þ 3D lenses over one eye (middle panel). 22,46 The fellow eyes viewed through zero-powered lenses.…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
“…The time course and efficiency of emmetropization is also not altered by foveal ablation. In addition, laser ablation of the fovea does not prevent the eye from becoming myopic in response to either optically induced hyperopic defocus (left) 53 or form deprivation (right). 55 Nor does foveal laser ablation interfere with the ability of the eye to recover from either induced myopia or hyperopia.…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is well known that central hyperopic defocus can cause myopia in chicks 15 and mice models 16 . In addition, experiments conducted by Smith et al [17][18][19] have shown that peripheral hyperopic defocus can cause myopic shift in monkeys. This is a herald of 'peripheral defocus theory' that implicates defocus at the peripheral retina as the trigger for myopia.…”
mentioning
confidence: 99%
“…Although Liu and Wildsoet used the chick as their model for myopia development, they demonstrated that the effective visual field which starts to alter refractive changes was about 12°or more from the visual axis. Smith and co-workers found that an image with hyperopic defocus at the location of 10.3°from the visual axis would also induce myopic development in monkey eyes [5]. It is very interesting to show that the sensitive zone in the eye for refractive development is the paracentral to peripheral retina, and the most impaired retinal region in myopia is also the same retinal region.…”
mentioning
confidence: 96%